Simultaneous three‐dimensional elemental mapping of Hollandite and Pyrochlore material phases in ceramic waste form materials. Issue 9 (12th March 2019) - Damian, Peter Joseph C.; Cocco, Alex P.; Wrubel, Jacob A.; Hong, Tao; Bordia, Rajendra K.; Liu, Yijin; Pianetta, Piero; Amoroso, Jake W.; Brinkman, Kyle S.; Chiu, Wilson K. S.
Abstract: Differential X‐ray absorption contrast tomography was performed on model ceramic composite systems to image the 3D spatial distributions of Ga and Nd containing phases. The model material systems were fabricated such that they contained two constituent phases. Ga–doped Ba hollandite (Ba1.33 Ga2.66 Ti5.34 O16 ), and pyrochlore (Nd2 Ti2 O7 ) which are under consideration as nuclear waste immobilization matrices. Two complementary techniques have been used to characterize the 3D distribution of phases. The analysis suggests that the 3D spatial distributions of hollandite and pyrochlore can be readily identified through the distributions Ga and Nd, respectively. These results represent a critical development towards characterizing the complex microstructure inherent to practical materials such as multiphase ceramic composite waste forms. Moreover, these methods can be applied to elucidate microstructural features that fundamentally determine the performance and properties of complex systems, which is central to the design of durable waste forms as well as many other real materials such fuel cells, batteries, ultra‐high temperature ceramics.